CMLHS lives up to expectation - Marziah, Ramli (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
26 April 2012. CMLHS was on high when Ezihaslinda Ngah and Hafizoah Kassim grabbed the women’s double crown in Badminton Tournament hosted by Chemical and Natural Resources Engineering (FKKSA), held from 23 – 26 April at the Sports Complex.